Introducing methadone maintenance therapy into Ukrainian prisons: a qualitative study of criminal subculture, Russia’s full-scale invasion, and contested methadone objects - Ponticiello, Matthew; Azbel, Lyu; Tate, Mary M.; Bromberg, Daniel J.; Pykalo, Iryna; Kiriazova, Tetiana; Saichuk, Natalya; Altice, Frederick L. (Frontiers in Psychiatry, 2023)
Background After pilot testing, methadone was newly being introduced into Ukrainian prisons in 2021 as part of a national scale-up strategy to treat opioid use disorder and prevent transmission of HIV and HCV infections. Opioid agonist therapy (OAT) scale-up in Eastern Europe and Central Asia prisons has been hampered by varying levels of influence of criminal subculture, an extralegal informal governance by a social hierarchy that operates in parallel to formal prison authorities. This study examined the socio-environmental factors influencing the uptake of methadone treatment in Ukrainian prisons, including changes that evolved during Russia’s full-scale invasion of Ukraine and the displacement of people deprived of liberty (PDL) from conflict to non-conflict regions. Methods In-depth qualitative interviews (N = 37) were conducted from January 2021 to October 2022 in the only two Ukrainian prisons where methadone was being introduced with PDL (N = 18). These two prisons continued to provide methadone after the full-scale invasion. Former PDL (N = 4) were also interviewed and prison staff (N = 15). Interviews were audio-recorded, transcribed, and translated into English. Four authors independently reviewed, coded, and applied a phenomenological framework for data analysis, delineating themes related to criminal subculture, drug use, methadone uptake, and evolving changes during the Russian invasion. Findings Criminal subculture perceptions varied, with some seeing it as strongly discouraging drug use among certain groups, while others described it as a residual and weak influence from a more distant past. The influence of the subculture on methadone treatment uptake, however, was less clear. PDL and prison staff struggled to identify and articulate differences between illicit street-bought methadone, used recreationally, and medically prescribed methadone. Thus, the meaning of “methadone” varies in interpretation as it is being introduced, making it potentially conflicting for patients to opt into this evidence-based treatment. As Russia invaded Ukraine in 2022, PDL from conflict zones were transferred to non-conflict regions where methadone was being introduced. The prison environment became more enabling for PDL to start methadone as they were segregated and not subject to the existing criminal subculture’s rules and lacked the social ties necessary to procure drugs illegally. Conclusion It appears that the criminal subculture is variable and evolving in Ukrainian prisons and appears to be impacted differently by the invasion of Russia. As methadone scale-up in prisons expands, it will be important to distinguish the meaning of methadone perpetuated negatively by the prison subculture versus that in which it is intended as a medical treatment by the formal prison authorities. The current invasion of Ukraine by Russia provides a potential disruption to alter this course.